Distribution, trends and threats to Eastern Taiga Bean Goose Anser fabalis middendorffii in the River Lena basin, East Siberia - Degtyarev, Victor G. (Wildfowl, 2024)
Recent studies suggest that the Eastern Taiga Bean Goose Anser fabalis middendorffii is showing accelerated declines in abundance over the last 20 years, despite protection from hunting in the River Lena basin, northeast Russia. An understanding of its distribution and current threats throughout its breeding range therefore is required for the effective conservation of this subspecies, some of which is provided here through field research, together with a review of scientific publications and reports from local people. Currently, the geese occupy streams in remote sub-montane and plateau areas, a distribution pattern unlikely to be natural but the result of long-term overhunting. Historically-occupied habitats were associated with lowland, large river valleys which used to form the major part of its breeding grounds, but the improvement and accessibility of weapons and transportation led to increasing fragmentation of the Eastern Taiga Bean Goose’s breeding range, so that the large rivers and more accessible reaches of the streams are no longer used for nesting. Fishing and tourism can also have a negative effect on breeding by geese, factors which may continue to contribute to the decline of the Eastern Taiga Bean Goose to this day. More rigorous enforcement of anti-poaching legislation, and modification to hunting and protected area regulation, should be undertaken to reduce unintentional shooting of Taiga Bean Geese by law-abiding hunters. Recent observations and reports from local people suggest that arrival in autumn of tundra-breeding geese migrating through the Eastern Taiga Bean Goose’s breeding range is now later than in the 20th century. Data therefore are needed to inform adjustments to the hunting regulations, for instance by developing telemetry studies to track the timing and stopovers used by of birds during migration, as well as providing insights into their movements on the breeding and wintering grounds. Under the current flexible protection regime, the most important streams used by Eastern Taiga Bean Geese in protected areas should be closed to any visitors during the summer months, particularly areas important for the geese and other species in the eastern Aldan highlands and on the Vilyuiskoe Plateau in eastern Siberia.